2017
DOI: 10.5430/jnep.v7n12p89
|View full text |Cite
|
Sign up to set email alerts
|

Impact of training program regarding first aid knowledge and practices among preparatory schools' teachers at Assiut City

Abstract: Teachers and children spend considerable time together within the school environment. Schools are places where one can find a noticeable risk of traumatic injuries. The study aimed to evaluate the impact of training program regarding first aid knowledge and practices among preparatory schools' teachers. Subjects and methods: Quasi-experimental study with one group pre/post test research design was used. Multistage random sample used to select the five preparatory schools and the participated teachers which inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
2
3
1
Order By: Relevance
“…With regards to training, one-third of the respondents have taken training on first aid in this study. Our finding is supported by the studies conducted among kindergarten teachers in Addis Ababa which were 32.2% (10), in China 30.8% (15), and Assiut City, Egypt 26.7% (12). Those participants who did not take any training on first aid were found to be less knowledgeable compared with those who had training on first aid (AOR=0.43, 95%CI ;(0.21, 0.87)).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With regards to training, one-third of the respondents have taken training on first aid in this study. Our finding is supported by the studies conducted among kindergarten teachers in Addis Ababa which were 32.2% (10), in China 30.8% (15), and Assiut City, Egypt 26.7% (12). Those participants who did not take any training on first aid were found to be less knowledgeable compared with those who had training on first aid (AOR=0.43, 95%CI ;(0.21, 0.87)).…”
Section: Discussionsupporting
confidence: 84%
“…The finding of this study is higher than the study conducted in Assiut city, Egypt among preparatory school teachers which found 97.3% teachers to have poor knowledge score on pretest (12) despite a significant improvement was recorded following a training 75.3% good performance. A similar finding was also reported in a study conducted in Isparta, Turkey among preschool teachers which found only 15.5% participants to have good knowledge on first aid (13).…”
Section: Discussioncontrasting
confidence: 84%
“…15 The findings of the study done by El-magrabi et al revealed that, there was statistical significant differences between total score of teachers" knowledge (p=0.000) in pre and immediate post-test which was similar to our study with only difference that post-test was not immediate but was conducted after a week. 16 Van-de-Velde et al in their systematic review study concluded that first aid programmes that also train participants to overcome inhibitors of emergency helping behaviour could lead to better help and higher helping rates. 10 This helping behaviour aspect was not part of our study but future studies can be planned where training on first aid along with helping behaviour will be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Egypt (39) and one in China (17) also showed poor knowledge before an educational intervention on first aid in case of scald, and then correct answers with statistical significance after the intervention. In Isparta, only 32.7% of teachers knew how to properly perform this procedure (5) .…”
Section: Discussionmentioning
confidence: 99%